Coherent control of birefringence and optical activity - Mousavi, Seyedmohammad A. (2018)
We show that polarization effects due to anisotropy and chirality affecting a wave propagating through a thin slab of material can be controlled by another electromagnetic wave. No nonlinearity of the metamaterial slab is required and the control can be exercised at arbitrarily low intensities. In proof-of-principle experiments with anisotropic and chiral microwave metamaterials, we show that manifestations of linear and circular birefringence and dichroism can be modulated by the control wave from their maximum value to zero.